Human Papiloma Virus in lung cancer tissue. Experience at the Calderon Guardia Hopsital - González Solano, Emmanuel (2012)
Background: The epidemiology of lung cancer, a major cause of morbidity throughout the world and the leading cause of mortality among adult men and women, has changed substantially in the past few years. Some of these changes can be explained by tobacco consumption, but there is also the possibility of other carcinogenic agents involved in lung cancer etiology, such as Human Papilloma Virus (HPV) and they have described a mechanism by which some of the viral structural proteins interfere with tumor suppressor genes, leading to uncontrolled and fast cellular proliferation. Methods: The objective of this study was to establish the prevalence of HPV in lung cancer (LC) tissue. The study population was a group of 110 patients with histologically confirmed LC. The biopsies of lung tissue where fixed in paraffin and formalin at the Calderon Guardia Hospital, Department of Pathology, from January 2002 to July 2009. The viral DNA was extracted using a system for fixed tissue -QIAmp DNA FFPE-, and the virus detection was done by multiple PCR differentiation on the molecular weight of the E6 gen that differs within genotypes. Results: The prevalence of HPV in LC was 4,5%. Most of the HPV types found were non-oncogenic Conclusions: The prevalence found is very low in comparison with other regions of the world. There was no association found between HPV and LC histology, gender, and tobacco use.